Is there a need for anthropometric standards in Olympic sports? A proposal for the kinanthropometric profile of elite flag football athletes - Talavera-Hernández, L. F.; Maceroni, C.; Travis-Carr, E. L.; Macgregor, L. J.; Vázquez-Villarreal, L. G.; Menargues-Ramírez, R.; Dergal-Irigoyen, M. P.; Reyes-Castillo, E.; Castro-Ávila, J. I.; Martínez-Sanz, J. M.; Rodriguez-Sanchez, N. (Frontiers in Nutrition, 2025)
Background: Body composition strongly influences the performance of flag football (FF) players, which makes anthropometric measurements important. With the growing popularity of FF, understanding body composition requirements for both male and female players is essential to help optimize their performance. Purpose: This study aimed to characterize and compare anthropometric and body composition profiles between male and female FF players across different playing positions. The study was conducted during the European Flag Football Championship organized by the International Federation of American Football (IFAF).